ELECTROMAGNETIC RADIATION ABSORBERS BASED ON POWDERED PEAT IN POLYMER HYDROGEL BINDER - D. V. Stoler; T. A. Pulko; N. V. Nasonova; Yu. V. Smirnov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The influence of the type and volume content of powdered peat on the shielding characteristics of composite materials was investigated in the frequency range of 8…12 GHz. It was shown, that the transmission and reflection coefficients slightly differ for various types of peat components and mainly depend on the volume content and the layer thickness. The transmission coefficient for the studied materials varies in the range of -4.5…-2.1 dB and the reflection coefficient - in the range of -12.2…-8.2 dB.